Big Tech Acquisitions and Innovation: An Empirical Assessment - Laureen de Barsy; Axel Gautier (Center for Economic Studies and ifo Institute (CESifo), 2024)
In the past 20 years, large digital platforms have made many acquisitions, mainly young and innovative startups. Few of them have been reviewed by competition authorities and little is known on their evolution after acquisition. This paper intends to fill in this gap by looking at the development of the technologies owned by the acquired firms. We focus on technologies protected by a patent and we investigate whether an acquisition by a big tech contributes to their development. For this analysis, we use patent citations as a proxy for the innovation effort by the acquirer. Our main result is to show that acquisition increases the innovation effort of the acquirer but only temporarily. After 1.5 year, there is no longer a significant impact of the acquisition on the acquirer's innovation effort. This decline is relatively larger when the acquired patent belongs to a core technology field of the acquiring firm or to a large patent portfolio. On the contrary, citations by the rest of the industry are not negatively affected by acquisition, which does not corroborate the idea that the acquired technology has reached its maturity.
Keywords: D43; G34; K21; L40; L86; 330; mergers; digital; big techs; innovation; patents; killer acquisitions